Product and Service Quality on Customer Satisfaction: Case Study at Merindu Cafe - Bagus Putra (PENTAHELIX: Jurnal Ilmiah Pengabdian Pariwisata, 2023)
This research aims to (1) find out how product quality influences customer satisfaction, (2) find out how service quality influences customer satisfaction, (3) find out how product quality and service quality influence customer satisfaction. This research is quantitative research. The population in this research is visitors who miss coffee. The samples taken were 81 respondents. The sampling technique used in this research is accidental sampling. Data collection techniques use questionnaires, interviews, and documentation. The data analysis technique used to answer the research hypothesis is multiple linear regression. The research results at a significance level of 5% show that: (1) there is an influence of product quality on customer satisfaction. This is proven by the calculated t value of 4.553 with a significance value of 0.000 which is smaller than 0.05 (0.000 < 0.05), and the regression coefficient has a positive value of 0.101. (2) there is an influence of service quality on customer satisfaction. This is proven by the calculated t value of 4.321 with a significance value of 0.000 which is smaller than 0.05 (0.000 < 0.05), and the regression coefficient has a positive value of 0.395. (3) there is a significant influence between the two independent variables, namely product quality and service quality simultaneously on customer satisfaction. This is proven by the calculated F value, namely 76.201 which is greater thanF table (3.11) with a significance level of 0.000 or sig 0.000, much smaller than 0.05.